Leverage Impact on Dividend Strategy: Insights from Institutional and Financial Dynamics - Made Gede Wirakusuma; Ni Made Dwi Ratnadi; Gerianta Wirawan Yasa; I Made Ryan Ananta Putra (Jurnal Ilmiah Akuntansi, 2024)
Dividend policy determines the allocation of profits between shareholder payouts and retained earnings. This study investigates the moderating role of leverage on the relationship between institutional ownership, cash position, and asset growth in shaping the dividend policies of companies within the raw goods, industrial, primary consumer goods, and non-primary consumer goods sectors. Despite previous research examining these variables individually, there is limited exploration of leverage as a moderating factor in these relationships, particularly within these sectors. Utilizing a sample of 240 companies and non-probability purposive sampling, the analysis employs the absolute difference test. Findings indicate that leverage does not enhance the positive effects of institutional ownership, cash position, and asset growth on dividend policy. These results contribute to agency and pecking order theories by highlighting the importance of institutional ownership in influencing management decisions on funding sources, particularly corporate debt, when determining dividend payments.